MODEL PEMBELAJARAN KOOPERATIF KANCING GEMERINCING UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI LINGKARAN - Rini Utami (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Student  law  achievment  in  mathematic  in  SMP  Negeri  4  Pekalongan  because  lack understanding  in  mathematic,  so  that  new  teaching  model  should  be  used  to  improve student’  achievment.  One  model  of  learning  that  can  be  applied  to  overcome  these problems is kancing gemerincing  cooperative learning model. Cooperative learning arises from the concept that student will more easliy find and understand difficult concept if they are dicussing with friends. In the activity kancing gemerincing, each member of the group gets achance to contribute their views and ideas and listen to other members. The place of the  research  is  SMP  Negeri  4  Pekalongan  .  The  subject  of  the  research  is  eight  grade students. Class action research with cycle model is used as the method of research. Method of  collecting  data  used  in  this  research  is  observation  and  test.  data  analysis used  is descriptive  analysis.  The  result  of  the  research  is  that  teaching  using  card  model  can improve students' comprehesion in material of circle. Kata  kunci  :  Kancing  Gemerincing Cooperative  Learning  Model,  Action  Research, Circle.